Delineating the psychological and behavioural factors of successful weight loss maintenance. Issue 1 (January 2020) - Levinge, Emily; Stapleton, Peta; Sabot, Debbie
Abstract: Overweight and obesity present alarming global health problems including detrimental health risks that call for effective interventions. Considerable research has examined behavioural and psychological factors associated with weight loss to advance the field of obesity and overweight. In line with the literature, this study aimed to develop a behavioural and psychological profile based on factors of personality, eating behaviours, emotional functioning, physical well-being, and psychopathology. The sample consisted of 105 community participants who had reduced their bodyweight by at least 10% and had either successfully maintained their weight loss for a minimum 12-month period ( n = 41) or had regained their weight loss within 12 months ( n = 64). Participants completed an online survey comprising demographic items and four empirical measures (Mini Marker Personality Scale, Patient Health Questionnaire, Three-Factor Eating Questionnaire-Revised, and a food screening tool) . Based on significant bivariate correlations results, four factors (fat intake, restrained eating, uncontrolled eating, and emotional eating) were entered into a binary logistic regression. Restrained eating was the only factor that significantly increased the likelihood of predicting successful long-term weight loss. Findings have implications for overweight and obesity future research, which may guide the direction of obesity and overweight treatments. Abstract : Psychology; Obesity; Overweight; Psychological; Behavioural; Weight maintenance; Restrained eating